2008
DOI: 10.1097/gme.0b013e31805fea75
|View full text |Cite
|
Sign up to set email alerts
|

Childhood abuse or neglect is associated with increased vasomotor symptom reporting among midlife women

Abstract: Objectives-This study tested the hypothesis that women exposed to childhood abuse or neglect would have an increased likelihood of reporting hot flashes and night sweats during the menopausal transition.Design-This hypothesis was evaluated in 332 white and African American women participating in the Study of Women's Health Across the Nation Mental Health Study, a prospective investigation of women transitioning through menopause. Childhood abuse and neglect were measured once with the Child Trauma Questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 66 publications
1
56
0
Order By: Relevance
“…Another aspect of the ACE-sleep association that is unique to women is the role of vasomotor symptoms of menopause. Thurston et al [59] studied the association between childhood abuse or neglect and vasomotor symptoms, which often affect sleep quality. The authors found that women with any child abuse or neglect had 1.7 (95% CI = 1.2-2.4) times the odds of reporting hot flashes and 1.8 (95% CI = 1.3-2.4) times the odds of reporting night sweats compared with women without a history of child abuse or neglect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another aspect of the ACE-sleep association that is unique to women is the role of vasomotor symptoms of menopause. Thurston et al [59] studied the association between childhood abuse or neglect and vasomotor symptoms, which often affect sleep quality. The authors found that women with any child abuse or neglect had 1.7 (95% CI = 1.2-2.4) times the odds of reporting hot flashes and 1.8 (95% CI = 1.3-2.4) times the odds of reporting night sweats compared with women without a history of child abuse or neglect.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that women with any child abuse or neglect had 1.7 (95% CI = 1.2-2.4) times the odds of reporting hot flashes and 1.8 (95% CI = 1.3-2.4) times the odds of reporting night sweats compared with women without a history of child abuse or neglect. Furthermore, these associations were statistically significantly stronger in African American women than in White women, further indicating the importance of studying racial/ethnic disparities in the association between ACEs and sleep [59]. …”
Section: Discussionmentioning
confidence: 99%
“…77 Life events as other possible effectors on mental health were explored in association with HFs in a limited number of studies. Thurston et al, 79 in a longitudinal prospective study, found that childhood abuse or neglect was associated with an increased tendency to report HFs in adulthood. Park et al 80 concluded in their case-control study that mental workload under time pressure might be a risk factor for menopausal HFs (although the overall performance of most people was not affected by them).…”
Section: Mood Disordersmentioning
confidence: 99%
“…Studies of midlife have also suggested that psycho-social stress is a significant correlate of symptom frequencies in Canada (Kaufert et al 1992), the UK (Kuh et al 1997), the U.S. (McKinlay et al 1987;Thurston et al 2008), Spain (Sievert et al 2007b), Japan (Igarashi et al 2000), and Chile (Binfa et al 2004). …”
Section: Introductionmentioning
confidence: 99%